The Challenges Faced by The Suku Anak Dalam in Embracing Modern Progress - Merry Roseline Pasaribu; Dhoory Vineyara Sigiro (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Indonesia is home to diverse ethnic groups with distinct customs and ways of life—traditions that risk erosion due to technological and modern advancements. This is particularly true for the Suku Anak Dalam, a tribe whose survival depends on the forest as their source of livelihood and shelter. This sociological-descriptive study examines the lives of the Suku Anak Dalam, focusing on how they sustain themselves and how the government acts to protect their human rights. Data was gathered from a former *tumenggung* (tribal leader) and community members who have successfully integrated into the surrounding environment. The findings reveal that the Suku Anak Dalam are facing a precarious situation; their traditional sources of livelihood are dwindling as their lands are converted into oil palm plantations owned by licensed companies. Consequently, they rely on collecting fallen palm fruit, living in constant fear and often being branded as thieves. Although government programs exist to provide housing for the tribe, many members remain unwilling to leave the forest, and recently, members of the Suku Anak Dalam have even been implicated in child abduction cases.